Risk Factors for Post-infectious Bronchiolitis Obliterans in Children: A Systematic Review and Meta-Analysis - Liu, Die; Liu, Jing; Zhang, Lipeng; Chen, Yuanmei; Zhang, Qi (Frontiers in Pediatrics, 2022)
Background： Post-infectious bronchiolitis obliterans (PIBO) is a long-term sequelae after an initial insult to the lower respiratory tract. A comprehensive understanding of the factors that contribute to a high risk of developing PIBO is important to help define therapeutic strategies and improve prognosis. Methods： We performed a systematic review of published literature available in the online databases including PubMed, Embase, Web of Science, CNKI, Wan fang, VIP, with the last search updated on January 27, 2022. Observational studies and case-control studies that provide sufficient data to examine associations between potential risk factors and PIBO were included. Pooled odds ratio (OR) or mean difference (MD) with 95% confidence interval (CI) and heterogeneity were calculated. Results： A total of 14 risk factors were selected from 9 studies included in the analysis. The strongest risk factors were hypoxemia, mechanical ventilation, tachypnea, wheezing. Hypoxemia conferred the greatest risk with pooled OR of 21.54 (95% CI 10.00–46.36, p< 0.001). Mechanical ventilation ranked second (pooled OR 14.61, 95% CI 7.53–28.35, p< 0.001). Use of γ-globulin、use of glucocorticoids、co-infection of bacteria 、a history of wheezing and male were other prominent risk factors. The effects of premature birth, allergic rhinitis, and imaging finding (Pulmonary consolidation, Atelectasis, Pleural effusion) are less clear and require further confirmation. Cases that developing PIBO had a lower age compared with controls (MD, -8.76 months, 95% CI, -16.50 to -1.02, p=0.03). No significant differences were observed in the duration of fever (MD,1.17days, 95% CI, -0.07 to 3.54, p=0.06). Children diagnosed PIBO had higher LDH levels (MD, 264.69U/L, 95% CI, 67.43 to 461.74, p=0.008) and duration of hospitalization (MD, 4.50 days, 95% CI, 2.63 to 6.37, p< 0.001). Conclusion： In this study, we found that the strongest risk factors for PIBO were hypoxemia, mechanical ventilation, tachypnea, wheezing. Use of glucocorticoids、Use of γ-globulin、co-infection of bacteria、a history of wheezing and male may also play a role. The factors discussed above can inform the generation of a clinical prediction model for the developing PIBO in children.